Competency Analysis of The Graduate of Vocational High School Using Dual Response Surveys - Lutfia Yasmin; Anni Faridah; Asmar Yulastri (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2019)
The problem in this research is that there are still graduates of Vocational High School No. 9 Padang who are unemployed after graduating. This study aims to analyze the competencies of culinary graduation at Vocational High School No. 9 Padang. This research is a quantitative study using the need assessment instrument with the dual-response survey technique. The results of the discrepancy analysis show that there is no high gap between the competencies of Vocational High School No. 9 Padang graduates and the competencies expected by the industry. The results of the direction analysis show that all the gap categories are in a low category, so it can be concluded that there is no high gap between the competencies of graduates of Vocational High School No. 9 Padang and the competencies expected by the industry. Based on the results of the priority analysis, it is known that there are differences in priority indicators in the three industries. Based on the research findings, it can be concluded that the graduates of culinary in Vocational High School No. 9 Padang have good competence based on an industry perspective.